Harvard business review on aligning technology with strategy (Boston, 2011)
If you need the best practices and ideas for unleashing technology's strategic potential--but don't have time to find them--this book is for you.
Keywords: Kế hoạch chiến lược,Information technology,Strategic planning,Công nghệ Thông tin; Management,Quản lý